Evaluation of teaching performance by university students of social and administrative sciences: a comparative study - Henriquez Ritchie, Patricio Sebastián; Pérez-Morán, Juan Carlos; del Cid García, Carlos Javier; Boroel Cervantes, Brenda (Frontiers in Education, 2025)
The purpose of this study is to measure higher education students' perceptions of their teachers' performance, as well as to analyze differences by sex, age, type of degree, and academic stage. To this end, the responses of 1,422 students from a higher education institution in northwestern Mexico who completed the EEDDocente 2023-1 were analyzed. The properties of the instrument's measurement model were verified. In this sense, the original three-factor model was reconfigured by a two-factor solution. The two-factor model explains 68% of the observed variance and has adequate fit indices (x2 = 2,661.58, df = 989, p < 0.0, CFI = 0.995, TLI = 0.995, GFI = 0.993, NFI = 0.993, RMSEA = 0.034 [IC 95% = 0.033–0.035], SRMR = 0.051). The measurement model was also found to be invariant across the grouping variables. Overall, the items had high mean scores (mean > 3), suggesting that students perceived their teachers as highly effective. Significant differences (p < 0.01) were reported between participants' scores based on their age and academic stage; however, the effect size was low (η2 < 0.10). Finally, the contributions, scope, and limitations of the study are discussed.